Alteração das funções sensoriais de olfato e paladar e seus correlatos clínicos e funcionais em indivíduos com Covid-19 - Nascimento, Maiara Alves do (2021)
Objetivo: investigar cómo los cambios autoinformados en las funciones sensoriales del olfato y el gusto en común con COVID-19 y sus correlaciones y clínicas. Metodología: se trata de una investigación descriptiva y analítica realizada mediante un formulario online, utilizando los recursos de la plataforma Google Docs®. El formulario se estructuró a partir de un cuestionario sociodemográfico, un cuestionario de investigación clínica y un cuestionario de investigación de síntomas autoinformados. Para la formación de la muestra se realizó un cálculo probabilístico, utilizando una referencia del 15% de la colección COVID-19 de un estudio previo, adoptando un nivel de confianza del 95% y un margen de error del 5%, alcanzando un total de 195 Participantes. Se percibe la posibilidad de pérdidas por fallas en la recolección de datos o por incumplimiento de los criterios de elegibilidad preseleccionados, la muestra final estuvo conformada por 210 pertenecientes, mayores de 18 años y que tenían un diagnóstico positivo para COVID-19. Results: the demographics of the data showed age ranging from 18 to 79 years (mean ± 33.97), with a greater representation of females (79.5%) and a predominance of participation in the state of Paraíba (71.4%) . The prevalence of anosmia and ageusia in the general population was 86.2%, with anosmia being present in 84.8%, and ageusia in 77.6%. In addition to these, the most reported symptoms were headache (80%), fatigue / tiredness (70.5%), runny nose or stuffy nose (71.8%), muscle pain (70.3%), cough (55.2%), diarrhea (49.0%) sore throat (48.3%), fever (47.6%), and to a lesser extent the feeling of shortness of breath (27.1%). There was statistical significance in the analysis of the association between loss of smell and taste and the symptoms of cough, runny nose, headache and fatigue and the relationship between the symptom of shortness of breath and ageusia and the symptom of muscle pain and anosmia. The loss of sensory functions was evidenced predominantly in younger individuals and in the female sex, contributing to the alteration of appetite, pleasure and desire for food, increasing the time to finish a meal during the onset of the disease. It was also evidenced that 63.3% reported the absence of diseases preceding the infection by COVID-19. Conclusion: the alterations in the sensory functions of smell and taste behaved as an important factor to be considered in COVID-19 infection, as they are associated with other symptoms of the disease. It was also found that anosmia and ageusia contributed to changes in eating behavior.